Isolation, Solitude and Social Distancing for People Who Use Drugs: An Ethnographic Perspective - Roe, Laura; Proudfoot, Jesse; Tay Wee Teck, Joseph; Irvine, Richard D. G.; Frankland, Stan; Baldacchino, Alexander Mario (Frontiers in Psychiatry, 2021)
COVID-19 has resulted in deepened states of crisis and vulnerability for people who use drugs throughout Europe and across the world, with social distancing measures having far-reaching implications for everyday life. Prolonged periods of isolation and solitude are acknowledged within much addiction literature as negatively impacting the experiences of those in recovery, while also causing harm to active users – many of whom depend on social contact for the purchasing and taking of substances, as well as myriad forms of support. Solitude, however, is proposed by the authors as inherent within some aspects of substance use, far from particular to the current pandemic. Certain forms of substance use engender solitary experience, even where use is predicated upon the presence of others. Adopting a cross-disciplinary perspective, this paper takes as its focus the urgent changes wrought by the pandemic upon everyday life for people who use drugs, drawing on recent ethnographic fieldwork with substance users in Scotland. Beyond the current crises, the paper proposes solitude, and by extension isolation, as an analytical framework for better apprehending lived experiences of substance use.